2020
DOI: 10.1039/c9py01913h
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of miscible supramolecular network blends using DDA·AAD hydrogen-bonding interactions of pendent side-chains

Abstract: Miscible blends of poly(methyl methacrylate) and polystyrene polymers are assembled through triple hydrogen bonding between complementary ureidoimidazole and amidoisocytosine heterodimers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…62 Furthermore, in hydrogenbonded polymer blends, the strength of H-bonding dictated by polymer chemistries also affects the blend miscibility, structure, and properties. For example, Wilson and co-workers showed that copolymer blends consisting of poly(methyl methacrylate) (PMMA) and polystyrene (PS) functionalized with high-affinity H-bonding motifs ureidoimidazole (UIM) and amidoisocytosine (AIC), respectively, 63 formed miscible supramolecular networks at a lower molar ratio of functionalized comonomers compared to PMMA and PS blends functionalized with low-affinity H-bonding motifs phenylureidopyrimidine (PUPY) and diamidopyridine (DAP), respectively. 64 Similarly, previous work focused on binary blends with the same hydrogen-bond-accepting polymer chemistry (poly(N-acryloyl piperidine) (PAP)) but different hydrogen-bond-donating polymers, namely, (poly(acrylic acid) (PAA), poly(vinyl alcohol) (PVA), or poly(4-vinyl phenol) (PVPh)), showed that the linker group chemistry dictated the donating strength of the −OH donor group and the distribution of hydrogen bonds.…”
Section: Introductionmentioning
confidence: 99%
“…62 Furthermore, in hydrogenbonded polymer blends, the strength of H-bonding dictated by polymer chemistries also affects the blend miscibility, structure, and properties. For example, Wilson and co-workers showed that copolymer blends consisting of poly(methyl methacrylate) (PMMA) and polystyrene (PS) functionalized with high-affinity H-bonding motifs ureidoimidazole (UIM) and amidoisocytosine (AIC), respectively, 63 formed miscible supramolecular networks at a lower molar ratio of functionalized comonomers compared to PMMA and PS blends functionalized with low-affinity H-bonding motifs phenylureidopyrimidine (PUPY) and diamidopyridine (DAP), respectively. 64 Similarly, previous work focused on binary blends with the same hydrogen-bond-accepting polymer chemistry (poly(N-acryloyl piperidine) (PAP)) but different hydrogen-bond-donating polymers, namely, (poly(acrylic acid) (PAA), poly(vinyl alcohol) (PVA), or poly(4-vinyl phenol) (PVPh)), showed that the linker group chemistry dictated the donating strength of the −OH donor group and the distribution of hydrogen bonds.…”
Section: Introductionmentioning
confidence: 99%
“…Herein, the strongly dimerizing UPy groups complemented with lateral stacking of urea moieties , and high glass transition temperatures ( T g ) of polynorbornene ensured the formation of stable, intramolecularly crosslinked nanoparticles. Weak hydrogen bonding motifs, in contrast, exhibit fast exchange dynamics, resulting in higher probabilities of intermolecular crosslinking, and are therefore less suitable for this processing approach . The solvent generally plays a crucial role in this process as strong hydrogen bonding complexes should be formed while at the same time interparticle aggregation should be prevented.…”
Section: Introductionmentioning
confidence: 99%